Flexural capacity of long-span transversely loaded hollow block masonry walls. (30th September 2019) - Ardito, Raffaele; Taliercio, Alberto
Highlights: Four-point bending tests on long-span unreinforced and reinforced masonry walls, using traditional and innovative stirrups, were carried out. Eurocode 6 underestimates the flexural capacity of low-rise unreinforced walls. In reinforced tall walls, traditional stirrups perform better than innovative stirrups. Limit analysis underestimates the flexural capacity if only the reinforced cores are taken into account. A finite element model is developed to predict the flexural capacity. Abstract: An experimental programme was carried out on long-span masonry walls made of hollow concrete blocks. Both low-rise unreinforced walls and tall reinforced walls were subjected to four-point bending tests. The tests aim at obtaining indications on the flexural capacity of partially grouted, long-span masonry walls, which basically consist of unreinforced walls laterally supported by reinforced columns, and are mainly subjected to transverse loads. The tests on reinforced walls were also intended to compare the effectiveness of two types of reinforcement (a traditional one and an innovative one in which stirrups are replaced by metal strips welded to the longitudinal rebars) on the flexural capacity. Eurocode 6 is found to strongly underestimate the experimental flexural strength of the unreinforced walls. The traditional reinforcement was found to be more effective than the innovative one. Eventually, a finite element model of the reinforced walls was developed to try and capture their failure modes. Upon a careful calibration, the numerical model is able to match the experimental ultimate load, although the real transverse displacements cannot be correctly captured.